Case report: Obstructive jaundice caused by biliary cystadenoma - Li, Yun-cheng; Shi, An-da; Li, Kang-shuai (Frontiers in Oncology, 2023)
Biliary cystadenoma (also called mucinous cystic neoplasm with low-grade intraepithelial neoplasia) is a rare cystic tumor that arises from the biliary epithelium. The cause of biliary cystadenoma is still unclear. Jaundice is a rare presentation of intrahepatic biliary cystadenoma, which can lead to a diagnostic dilemma. Herein, we present a case of intrahepatic biliary cystadenoma that primarily exhibited as jaundice. A 56-year-old woman has suffered from yellow staining of her skin and sclera for more than 1 month. She had a poor appetite and mild epigastric pain. Laboratory examination showed elevated levels of total bilirubin and elevated carbohydrate antigen 19-9 (CA19-9). A contrast-enhanced computed tomography of the abdomen showed a 7.4 * 5.3-cm, oval, low-density lesion in the left liver parenchyma with a clear boundary and visible septa. The common bile duct was obviously dilated with wall thickening. On magnetic resonance imaging, the lesion in the liver showed a multilocular cystic, unenhanced long T2 signal. There was local thickening of the common bile duct wall with short T2-like filling defects and high signal intensity on diffusion-weighted imaging (DWI). The patient had no history of other malignant tumors and adjuvant therapy such as radiotherapy and chemotherapy. She was clinically suspected of having either biliary cystadenoma or a malignancy; hence, resection was performed. Macroscopically, the excised tissue specimen showed a polypoid mass in the common bile duct, which extended along the bile duct to the intrahepatic bile duct. There was a cystic and solid mass in the left liver with yellow turbid fluid, which was associated with the polypoid mass in the common bile duct. Histopathology suggests mucinous cystadenoma of the liver and hilar bile duct. The differential diagnosis of biliary cystadenoma and treatment selection have been discussed.